Statistical rules of thumb - Van Belle, Gerald (John Wiley & Sons, 2002)
Statistics-in one handy reference Not even the most brilliant statistician can instantly recall every rule and concept that forms the daily bread of statistical work. For every practitioner and student without a photographic memory, here is an eminently practical, easy-to-use, concise sourcebook that puts a broad range of topics instantly at your fingertips. Sensibly organized for quick reference, Statistical Rules of Thumb compiles simple rules that are widely applicable, robust, and elegant, and that capture key statistical concepts. Explaining the justification for each rule, this handbook also conveys the various possibilities that statisticians must think of when designing and conducting a study or analyzing its data. It provides a framework for considering such aspects of statistical work as: * Randomness and statistical models * Sample size * Covariation * Epidemiology * Environmental studies * Designing, conducting, and analyzing studies * Words, tables, and graphs * Consulting Handy and reliable, this all-in-one reference should be the trusted companion of every statistician.
Wiley series in probability and statistics
Keywords: Statistics as Topic; matematika; statistika jako téma; statistika, zdravotnická statistika; Mathematics